Toxicity Assessment of Waters from Rio Doce after the Fundão Dam Rupture to Zebrafish Embryos - de Figueiredo Eufrasio Pauly, Guacira [UNESP]; Yamamoto, Flávia Yoshie [UNESP]; de Souza Abessa, Denis Moledo [UNESP] (Springer Nature, 2025)
The collapse of the Fundão Dam in 2015 caused strong alterations of physical–chemical properties of water bodies in the Rio Doce Basin, including the release of large quantities of metals. This study aimed to evaluate whether water samples collected along the Doce River after dam failure could affect the development of Danio rerio embryos. Water samples were collected immediately and 6 months after the rupture at multiple sites distributed across the river basin, and toxicity tests were conducted using recently fertilized eggs, in 24-well plates. The concentrations of As, Cd, Mn, and Ni in water samples collected immediately after the dam rupture exceeded the limits established by federal standards. No significant lethal or sublethal effects were observed in D. rerio embryos exposed to water samples in both sampling surveys. Based on our results, we hypothesized that although the concentrations of some elements were high, metals were likely not or poorly bioavailable, causing no significant changes in the exposed organisms.
Keywords: Chronic effects; Danio rerio; Metals; Pollution